HAART has no major impact on hematological and plasma bilirubin changes in HIV-infected patients with congenital G-6-PD deficiency - Sakorn Pornprasert (2018)
Hematological effects of antiretroviral (ARV) drugs in HIV-infected patients with glucose-6-phosphate dehydrogenase (G-6-PD) deficiency are unclear. The aim of this study was to assess effects of highly active antiretroviral therapy (HAART) on hematological and plasma bilirubin changes in these patients. A hundred and nine HIV-infected Thai patients were tested for G-6-PD deficiency and its variant by using fluorescent spot test and polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) analysis, accordingly. Changes of hematological parameters and plasma bilirubin at baseline and 6 months of HAART were analyzed in G-6-PD deficiency patients. G-6- PD deficiency was found in 10 (9.17%) patients and G-6-PD Canton1376G>T was the most frequent. Of these, 3 patients had coinheritance of G-6-PD deficiency and thalassemia. Increased mean levels of lymphocyte counts, CD4+ T-cells, mean corpuscular hemoglobin (MCH) and hemoglobin from baseline to 6 months of HAART were observed. Whereas, mean levels of total bilirubin and direct bilirubin at baseline were not significantly different from those at 6 months of HAART. Therefore, HAART did not cause hemolytic anemia and hyperbilirubinemia in HIV-infected patients with G-6- PD deficiency. On the other hand, the effective use of HAART is associated with improvements in hemoglobin and MCH levels of these patients. © 2013 Bentham Science Publishers.